Business networks and organizational resilience : relational capital of companies and times of crisis - Walecka, Anna Aleksandra (Routledge, 2026)
Business Networks and Organizational Resilience: Relational Capital of Companies and Times of Crisis is a comprehensive monograph that investigates the interplay between a company's relational capital and its ability to withstand and rebound from crises.Drawing on theoretical frameworks and empirical research, this book explores how relational capital influences organizational resilience in times of adversity, offering valuable insights for both scholars and practitioners. Through a blend of original research and empirical analysis conducted in two stages - the initial study in 2018 and its validation in 2024 - this monograph uncovers the intricate relationship between a company's relational capital and its resilience to turbulent circumstances.Readers will gain a deep understanding of the fundamental role of relational capital in crisis management and learn practical strategies for enhancing organizational resilience. The book provides actionable recommendations for measuring and managing relational capital effectively, equipping readers with the tools they need to safeguard their organizations from potential crises and navigate challenges with confidence.This book is essential reading for scholars and researchers seeking to deepen their understanding of relational capital and crisis management. Business practitioners, including entrepreneurs and organizational leaders, will also find valuable insights and actionable recommendations for improving organizational resilience. With its practical guidance and scholarly rigor, this book serves as a valuable resource for anyone interested in the intersection of relational capital and crisis management, bridging the gap between theory and practice in this critical area of study.
Keywords: Business networks.; Organizational resilience.; elektronické knihy; electronic books